The Sheikhsof Islam and Their Role in the Establishment of the Ottoman State (1876-1909) - Hussein, Riyad Khalil; Najm, Badr Lafta (Journal of Posthumanism, 2025)
In this research, the topic ofIslam and their Role in the Establishment of the Othoman State (1876-1909) was addressed. The historical method was applied. The study found that Sheikh Islam was an obedient tool in the hands of the Caliph, and he was certifying what the Caliph needed from fatwas. Among the most important sheikhs of Islam during the study period (1876-1909) were Sheikh Mohammed Sharif, who died for the second time in 1798, and Sheikh Mustafa Sabri Tuqadi, who assumed the sheikdom four times, During this period, Sheikh Islam played a distinctive role in reforming the state and influencing the decision-making in political, religious and social matters, as Sheikh Islam was a factor of strength for the state through his fatwas, especially in difficult times in the history of the Ottoman Empire.